Social Norms and Selectivity: Effects of Norms of Open-Mindedness on Content Selection and Affective Polarization. Issue 4 (3rd July 2020) - Wojcieszak, Magdalena; Winter, Stephan; Yu, Xudong
ABSTRACT: Given the polarizing effects of exposure to like-minded political information and the alleged societal benefits of exposure to diverse and dissimilar perspectives, we examine how to promote the selection of balanced and counter-attitudinal political content, thereby minimizing affective polarization. Two online experiments on American partisans ( N = 389 and N = 1378) tested the influence of social norms promoting open-mindedness. Study 1 focused on supporters and opponents of President Trump, showing that highlighting social norm of open-mindedness (vs. close-mindedness) in the general public increased exposure to balanced articles. Study 2, which focused on Democrats vs. Republicans and on the social norms among one's partisan ingroup, showed that highlighting ingroup open-mindedness (vs. control) enhanced counter-attitudinal exposure and indirectly attenuated several indicators of affective polarization. We discuss theoretical and practical implications for informed citizenship in an era of abundant media choice.